Nutritional Status of under 5-year Children in selected Community of Sindhupalchowk - Bhandari, Bhawana; Thapa, Rojina; Dhakal K.C., Muna; Chaudhary, Kiran; Dangi, Pratikshya (Academia Research Journal, 2026)
In Nepal, malnutrition emerged as a public health concern. Children's nutritional status is one of the main indicators of their survival and can be used as a key indicator to track their health. The purpose of the study was to evaluate the nutritional status of children under the age of five. A quantitative, descriptive, cross-sectional study design was carried out from 2080/7/19 to 2080/8/24 to determine the prevalence of nutritional status of Under 5 children. Total number of children (N) was 102 between 12 months to 59 months of age group. Non-probability, total enumerative sampling technique was used to determine the samples in the study. The prevalence of malnutrition was assessed by three standard anthropometric indicators: underweight, stunting and wasting, following WHO guidelines and cut-off points. The Statistical Package for Social Science (SPSS), version 20, was used for data analysis. Data analysis was done using descriptive statistics. Most of the respondents 85(83.3%) were Mild Underweight, almost three- fourth respondents 88(86%) were mild stunting, 3(3%) were moderate stunting, more than four-fifth 92(92%) were mild wasting, 3(3%) were obese. There was increase prevalence of moderate stunting, mild wasting, and mild underweight. Periodic assessment of growth and development, awareness regarding food preparation and feeding practices among parents of under 5 year children, monitoring and supervision is essential to prevent malnutrition in sustainable way